Research progress on the regulation of craniofacial development and malformation by fibroblast growth factor 8 - CAO Xiaoling; XIE Jing; ZHOU Xuedong (口腔疾病防治, 2022)
Fibroblast growth factor 8 (FGF8) is a kind of secretory polypeptide that has crucial roles in the development of various tissues and organs. Current studies have found that FGF8 can regulate the differentiation of cranial neural crest cells by activating the mitogen-activated protein kinase (MAPK) signaling pathway and affect the establishment of mandibular arch polarity and the development of craniofacial symmetry by regulating the expression of target genes. Cleft lip with or without cleft palate, ciliopathies, macrostomia and agnathia are four developmental malformations involving the craniofacial region that seriously affect the quality of life of patients. The abnormal FGF8 signal caused by gene mutation, abnormal protein conformation or expression is closely related to the occurrence of craniofacial malformations, but the molecular mechanism and signaling pathway underlying these malformations have not been fully elucidated. Craniofacial development is a complex process mediated by a variety of signaling molecules. In the future, the role of various signaling molecules in craniofacial development and malformations need to be explored to provide a new perspective and vision for the prevention and treatment of these craniofacial malformations.